Match-fixing in Portuguese football - Moriconi, M. (“Staying on Side: How to Stop Match-Fixing” - Project Conference, 2014)
The objectives are to know the perception and attitudes about match fixing of different collectives related to football industry in order to develop and serious and useful plan of prevention and recommendations. Match-fixing is not only a problem related to betting and Asian mafias, and I is dangerous and counter-productive to implement prevention strategies through a discourse that is not realistic for the social imaginary and do not respect the cultural narrative of the problem. · The activities implemented up to date and those planned until the end of the project The first steps of our research were going in depth into the bibliography and Portuguese history and understand which the particular problems and characteristics related with the phenomenon in Portugal are. During the first month, we have meeting with the League in order to establish a partnership in order to develop the training and prevention programs with institutional support. We failed due to our interest in develop an holistic analysis of the problem, and not restrict it only to match-fixing related with betting. We carried out a survey with referees in order to understand their perceptions and attitudes about the phenomenon. We are going to develop other surveys to know the opinion of fans and student of those careers related to sport and Sport Management. The Syndicate of Professional Football Players does not accept to promote a survey to know what players think about the problem. We carried out interviews with different sources following the method of the snow ball, in which a key informant recommends other key informant. We contact referees, ex referees, ex-football players, journalists, young players, father of young players, between others. We have personal meeting with leaders of the main institutions as well. We develop a close-door workshop with stakeholders to discuss institutional perceptions about the phenomenon, strengths and weaknesses of the existing legal and institutional framework to prevent, detect and sanction this type of practices. We had the participation of: Cabinet Chief – State Secretary for Sports and Youth; Legal advisor – Portugal League; Supporters’ ombudsman – Portuguese League; President - Referees Association; President - Syndicate of Players; President – Trainers Association; Portuguese Olympic Committee; Benfica Football School’s trainer; Sporting Football School’s Manager; Supporters direct Portuguese contact. The forma of the meeting was suggested for the League during our meeting in October, because Institutions do not fell free of speak of such a sensitive issue and in front of journalist. Other activities in agenda are: Production of prevention materials (February-March) to raise public awareness to the phenomenon; launch the project’s website in March; Train the trainers + Launch conference (April); Final conference: How to stop match-fixing in Portugal and abroad - Target groups, involved stakeholders All the stakeholders expressed their desire of participate in the activities and in the project. But participation does not mean collaboration. On the contrary, participation may determine an obstacle for the developing of a research. Our objective is to develop is to train the trainers of young players, but it is difficult because of the lack of institutional support. However, Results/recommendations/lessons learned 1 – Match fixing and lack of institutional transparency in football are important problems for social imaginary. Different stakeholders have a huge perception about the problem. However, it is not a problem related with betting but with football’s governance, links between sport and politicians, culture, economic and power differences between clubs, lack of transparency and institutional accountability. Match-fixing in Portugal aims, according to the perception of the population, to seek advantages in results. 2 – These are topics that generally appear in the press. Players, managers, trainers, and journalists often appear in the media doubting about the integrity of referees, managers and also of the international institution that govern football. However, we did not achieve support to publically discuss these problems in general terms with the main institutions. Football governance institutions accept to talk and fight again match fixing related to betting issues (something that does not apply to Portugal case) but without mention the historical problems that affected Portugal football some years ago, and that involved referees, managers and the League. 3 – In those football school which interview, there is not any campaign or training to prevent match-fixing. Young players do not talk about the phenomenon and are not aware of it. However, it is interesting to point out that some informant warned that young payers, fathers, coaches and managers recognized that referees tend to favour the top clubs. One important ex referees explained that, due to the difference of power between Portuguese’s clubs, it is difficult for a referee to be totally impartial, because unconsciously everybody knows where the power is. 4 – It is very important that all the stakeholders accept to talk about the essence of the phenomenon without restriction. On the contrary, their discourse strengthens the social imaginary that suppose that the negative of talk about the open reality is because there is something to hide. This type of limited strategy generates doubts and increases the perception of lack of volunteer to clean the general image of Portuguese football. 5 – Some stakeholders recognize fear to talk openly. In this sense, a key recommendation is the need to develop and implement effective whistleblowers legislation. Stakeholders do not perceive that there is protection for those who decide to denounce something related with match-fixing. 6 – The prevention discourse and strategy must take into account all these particularities. If the discourse is not realistic and do not include all the variables through which the social imaginary understand the problem, there will produce a dislocation with the meaning expected for the addressees. Define match-fixing as a problem of dangerous mafias which fix matches to bet in Asian and win and laundry money is a partial reality from Portuguese football.